Safety and privacy issues of electronic medical records - Fiza A.R.; Lizawati S.; Zuraini I.; Narayana S.G. (Indian Society for Education and Environment, 2023)
Objectives: The objective of this study is to review the safety and privacy issues of electronic medical records (EMR). Methods/Statistical Analysis: Secondary sources from Springer Link, Science Direct, Emerald Library, IEEE Explorer Digital Library, Taylor & Francis Online, and EBSCO host databases were used to reviews relevance articles. Findings: Intersection and inter-reliant components of the healthcare system as well technology-induced errors were documented as the safety issues in the EMR implementation. Additionally, information sharing and access control were recognized as the important privacy issues. This information will be valuable in identifying what should be considered on the implementation of appropriate security measures in safeguarding EMR. Application/Improvements: This review can be useful towards protecting privacy and safe implementation of EMR.